(untitled) (Revista Electrónica Calidad en la Educación Superior, 2025)
The aim of this article was to examine the general environment that Costa Rica offers for establishing a new specialized surgical medical center. The research involved a sector description, a generic PESTEL analysis (covering political, economic, social, technological, ecological, and legal factors), and the construction of a SWOT matrix (assessing internal factors [strengths and weaknesses] and external factors [opportunities and threats]). This study provided a comprehensive understanding of the factors influencing the establishment of a specialized health center of this kind. Additionally, it offered a solid foundation for strategic decision-making and the formulation of recommendations for the effective implementation of private health projects in Costa Rica. Through a descriptive methodology and the application of recognized strategic tools, the favorable environment Costa Rica offers for such private health projects was determined.